Metode System Literature Review Untuk Analisis Penggunaan TIK Sebagai Media Pembelajaran - Shafira Ramadiani Herliza; Faradiba Aurel Yasmin; Nanda Salma Zhafira; Razpa Arya Wardana (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
Information and communication technology or what is often called ICT is a device that can process and produce data or information. ICT can also be a tool and means to disseminate or publish such data and information. This study aims to determine the effectiveness and also the impact of using information and communication technology (ICT) as a medium in learning for students and staff to improve the quality of education in Indonesia. The method used in this study is the SLR or System Literature Review method. This SLR obtains data by collecting, analyzing, and also synthesizing previous literature that has the same research topic. This method can allow researchers to gain a comprehensive understanding where the data or information obtained includes evidence that is relevant and in accordance with the research topic. The results obtained from the formulation of the problem in this study are that ICT is an important use in improving teaching and learning activities in Indonesia. This increase in learning is certainly balanced by collaboration and good interaction between educators and students to use ICT in the process.